A Parent-Targeted and Mediated Video Intervention to Improve Uptake of Pain Treatment for Infants During Newborn Screening: A Pilot Randomized Controlled Trial. Issue 1 (January 2019) - Lavin Venegas, Carolina; Taljaard, Monica; Reszel, Jessica; Dunn, Sandra; Graham, Ian D.; Harrold, JoAnn; Larocque, Catherine; Nicholls, Becky; Nicholls, Stuart; O'Flaherty, Pat; Squires, Janet; Stevens, Bonnie; et al.
Abstract : Most newborns undergo newborn screening blood tests. Breastfeeding, skin-to-skin care, and sweet solutions effectively reduce pain; however, these strategies are inconsistently used. We conducted a 2-armed pilot randomized controlled trial in a mother-baby unit to examine the feasibility and acceptability of a parent-targeted and -mediated video demonstrating use of these pain-reducing strategies and to obtain preliminary effectiveness data on uptake of pain management. One hundred parent-newborn dyads were randomized to view the video or receive usual care (51 intervention and 49 control arm). Consent and attrition rates were 70% and 1%, respectively. All participants in the intervention arm received the intervention as planned and reported an intention to recommend the video and to use at least 1 pain treatment with breastfeeding or skin-to-skin care preferred over sucrose. In the intervention arm, 60% of newborns received at least 1 pain treatment compared with 67% in the control arm (absolute difference, −7%; 95% confidence interval, −26 to 12). The video was well accepted and feasible to show to parents. As there was no evidence of effect on the use of pain management, major modifications are required before launching a full-scale trial. Effective means to translate evidence-based pain knowledge is warranted.